Separability, Welfare Economics and the Theory of Second Best - Dusansky, Richard; Walsh, John (Review of Economic Studies, 1976)
Richard Dusansky, John Walsh; Separability, Welfare Economics and the Theory of Second Best, The Review of Economic Studies, Volume 43, Issue 1, 1 February 1976